COMBINATION VACCINES AGAINST KOIHERPES VIRUS AND Aeromonas hydrophila CO-INFECTION IN KOI AND COMMON CARP - Angela Mariana Lusiastuti; Hessy Novita; Lila Gardenia; Taukhid Taukhid; Habil Sven M. Bergmann (Indonesian Aquaculture Journal, 2020)
Co-infections occur when hosts are infected by two or more pathogens, either simultaneous or as a secondary infection. This research aimed to determine the best compositions of vaccine combinations and their protective efficacies against pathogens co-infection. This research was conducted in two stages. Firstly, surveys were conducted in three research areas: infected, high risk of infection, and virus free areas. Samples (three to five fish per pool) were collected from three fish farms per area. The basic antibody titer of fish from each farm was checked before and after vaccination as well as after the virus challenge in combination with the PCR result. The second stage of the research was conducted in the laboratory. Carp and koi fish were used to determine optimal vaccine combination and dosage for oral application. The results of this research showed that combination of KHV: Aeromonas hydrophila vaccines in the ratio of 1:2 and vaccine volume of 3 mL via the oral application gave higher titer antibody and efficacy against KHV and A. hydrophila. In conclusion, the combined vaccine offers an effective means of preventing the diseases, decreasing fish mortality, and simplifying the immunization schedule, which will eventually increase the overall health of farmed fish and benefit fish farmers and service extension officers. This research recommends that further development of the combined vaccines should be carried out, for example, overcoming the technical difficulties in its manufacturing.